Innovation of louvre daylighting system via using parametric design approach to enhance the daylight uniformity and stability in the deep-plan buildings - Eltaweel, Ahmad (2020)
For daylighting optimisation, shading devices are increasingly operated automatically to overcome the limitations of manual operation. Automated daylighting systems need to be controlled to maximise the benefits of daylight on the aspects of redirecting sunlight, occupant comfort and energy consumption. However, the conventional control methods focused on minimising adverse impacts of daylight, but they might fail to maximise the positive impacts of daylight. They may often inaccurately predict the position or angle of slats of louvre or blinds, resulting in the undesirable blockage of useful daylight needed. This PhD thesis puts forward an innovative control method for automated louvres to optimise the utilisation of daylight. The proposed control method can not only protect occupants from sunlight glare but also maximise daylight penetration into deep-plan office rooms based on algorithmic methods. The proposed control method is designed to reflect the incident sunlight onto the ceiling, where the reflected light acts as a source of light for illumination. The reflective mirrored slats are individually angled but rotated with the same angle, i.e., they respond to the sun altitude angles parametrically in individual heliotropic response so that they can reflect sunlight to the corresponding positions on a ceiling. Accordingly, this process can exploit the optimal use of natural daylight and provide shading simultaneously. In addition to the louvres, windows are the most common architectural elements widely used in office buildings to protect them from climate changes. Advanced glazing and other fenestration systems can further improve daylighting performance.